Answer:
x = 3
Explanation:
Solution for 16-3x=4+x equation:
Simplifying
16 + -3x = 4 + x
Solving
16 + -3x = 4 + x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-1x' to each side of the equation.
16 + -3x + -1x = 4 + x + -1x
Combine like terms: -3x + -1x = -4x
16 + -4x = 4 + x + -1x
Combine like terms: x + -1x = 0
16 + -4x = 4 + 0
16 + -4x = 4
Add '-16' to each side of the equation.
16 + -16 + -4x = 4 + -16
Combine like terms: 16 + -16 = 0
0 + -4x = 4 + -16
-4x = 4 + -16
Combine like terms: 4 + -16 = -12
-4x = -12
Divide each side by '-4'.
x = 3
Simplifying
x = 3Solution for 16-3x=4+x equation:
Simplifying
16 + -3x = 4 + x
Solving
16 + -3x = 4 + x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-1x' to each side of the equation.
16 + -3x + -1x = 4 + x + -1x
Combine like terms: -3x + -1x = -4x
16 + -4x = 4 + x + -1x
Combine like terms: x + -1x = 0
16 + -4x = 4 + 0
16 + -4x = 4
Add '-16' to each side of the equation.
16 + -16 + -4x = 4 + -16
Combine like terms: 16 + -16 = 0
0 + -4x = 4 + -16
-4x = 4 + -16
Combine like terms: 4 + -16 = -12
-4x = -12
Divide each side by '-4'.
x = 3
Simplifying
x = 3Solution for 16-3x=4+x equation:
Simplifying
16 + -3x = 4 + x
Solving
16 + -3x = 4 + x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-1x' to each side of the equation.
16 + -3x + -1x = 4 + x + -1x
Combine like terms: -3x + -1x = -4x
16 + -4x = 4 + x + -1x
Combine like terms: x + -1x = 0
16 + -4x = 4 + 0
16 + -4x = 4
Add '-16' to each side of the equation.
16 + -16 + -4x = 4 + -16
Combine like terms: 16 + -16 = 0
0 + -4x = 4 + -16
-4x = 4 + -16
Combine like terms: 4 + -16 = -12
-4x = -12
Divide each side by '-4'.
x = 3
Simplifying
x = 3